Substituting fossil-based with bio-based chemicals: the case of limonene as a greener pore expander for micellar templated silica - Sultan, Umair; Städtke, Katrin; Göpfert, Andreas; Lemmen, Daniel; Metwali, Ezzeldin; Maiti, Santanu; Schlumberger, Carola; Yokosawa, Tadahiro; Apeleo Zubiri, Benjamin; Spiecker, Erdmann; Vogel, Nicolas; Unruh, Tobias; et al. (RSC Sustainability, 2023)
Porous materials are widely used in applications such as adsorption, catalysis and separation. The use of expander molecules is a versatile route to enlarge the mesopore size in micellar templated mesoporous silica materials. Typical expanders used for this purpose are fossil-based organic molecules such as trimethylbenzene (TMB). In the course of making such syntheses greener and more sustainable, it is highly desirable to substitute such fossil-based chemicals with renewable ones. Here, we show that bio-based limonene can be used as an alternative expander molecule for the synthesis of large-pore templated silica. On the basis of electron microscopy, nitrogen physisorption and small angle X-ray scattering we show that the substitution of TMB by limonene leads to very similar material characteristics, reaching mean mesopore diameters of 17-19 nm. A comparative life-cycle assessment demonstrates the reduced environmental impact of limonene production from citrus peel waste compared to TMB production, supporting the call for more applications of renewable chemicals, ideally from waste-streams, also for the production of porous materials.
CRIS-Team Scopus Importer:2023-10-06